Bentuk Penyajian dan Fungsi Kidungan Malam Midodareni di Dukuh Biru Kecamatan Wonosari Kabupaten Klaten - Sasongko, Mohammad Brian; Manggala, Bondan Aji (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
Kidungan malam midodareni is a song or tembang macapat that is presented in a series of events on the eve of the marriage contract and panggih manten wedding ceremony in Dukuh Biru, Wonosari District, Klaten Regency, Central Java. Kidungan midodareni night is still preserved because people still consider it important and has social values. This article's writing is motivated by the younger generation's lack of interest in the midodareni night song tradition. The aim is to provide knowledge to the younger generation and the wider community about the general understanding of Kidungan Malam Midodareni, presentation procedures, functions, and how the midodareni night song tradition plays a role as a guardian of social stability in society. Qualitative research is used in this article using data observation, interviews, literature study, documentation, and interpretative descriptive analysis techniques. Richard Schechner's theoretical perspective is used to describe the form of presentation, while Alan P. Merriam's music function theory perspective is used to analyze the function of the midodareni night song. This research found that the presentation form of midodareni night song has three structures, namely (1) Preparation, (2) Performance, and 3) After the performance. The function of Kidungan Malam Midodareni is correlated in two parts, namely the function for the bride and groom and the function for the community; there are four elements of the position, namely: (1) as a means of communication, (2) as a means of community integrity, (3) as a means of entertainment, and (4) as a means of validating social institutions.